Peran Orang Tua dalam Menanamkan Sikap Disiplin Anak pada Masa New Normal - Fatkhur Rohman (Prodi PAI STAI Sumatera Medan, 2022)
This study aims to analyze the role of parents in instilling discipline in children in the new normal period at SDN 373 Sikara-Kara II, Natal District, Mandailing Natal Regency. The problem focuses on three things: the role of parents, constraints and solutions. This study uses a qualitative research method with a case study approach. The research informants comprised 15 parents with different educational backgrounds and children aged 7-12 years. The study results show that parents' role in instilling discipline in children during the new normal era is manifested in several ways: making simple rules, accustoming them to an orderly life, and setting an excellent example for children. In practice, parents also experience obstacles such as; limited time for parents to accompany their children and change the habits of children who are not suitable for the better. However, parents have solutions for dealing with these obstacles, such as sharing time between the roles of both parents in instilling discipline in children in the family, giving gifts to children who can carry out the rules that have been made, and establishing communication with teachers. So, cooperation is found in instilling discipline in children both in the family and school environments.